Characterization of the Changes in Cardiac Structure and Function in Mice Treated With Anthracyclines Using Serial Cardiac Magnetic Resonance Imaging. (December 2016) - Farhad, Hoshang; Staziaki, Pedro V.; Addison, Daniel; Coelho-Filho, Otavio R.; Shah, Ravi V.; Mitchell, Richard N.; Szilveszter, Balint; Abbasi, Siddique A.; Kwong, Raymond Y.; Scherrer-Crosbie, Marielle; Hoffmann, Udo; Jerosch-Herold, Michael; et al.
Abstract : Background—: Anthracyclines are cardiotoxic; however, there are limited data characterizing the serial changes in cardiac structure and function after anthracyclines. The aim of this study was to use cardiac magnetic resonance to characterize anthracycline-induced cardiotoxicity in mice. Methods and Results—: This was a longitudinal cardiac magnetic resonance and histological study of 45 wild-type male mice randomized to doxorubicin (n=30, 5 mg/kg of doxorubicin/week for 5 weeks) or placebo (n=15). A cardiac magnetic resonance was performed at baseline and at 5, 10, and 20 weeks after randomization. Measures of primary interest included left ventricular ejection fraction, myocardial edema (multiecho short-axis spin-echo acquisition), and myocardial fibrosis (Look-Locker gradient echo). In doxorubicin-treated mice versus placebo, there was an increase in myocardial edema at 5 weeks (T2 values of 32±4 versus 21±3 ms; P <0.05), followed by a reduction in left ventricular ejection fraction (54±6 versus 63±5%; P <0.05) and an increase in myocardial fibrosis (extracellular volume of 0.34±0.03 versus 0.27±0.03; P <0.05) at 10 weeks. There was a strong association between the early (5 weeks) increase in edema and the subacute (10 weeks) increase in fibrosis ( r =0.90; P <0.001). Both the increase in edema and fibrosis predicted the late doxorubicin-induced mortality in mice ( P <0.001). Conclusions—: Our data suggest that, in mice, anthracycline-induced cardiotoxicity is associated with an early increase in cardiac edema and a subsequent increase in myocardial fibrosis. The early increase in edema and subacute increase in fibrosis are strongly linked and are both predictive of late mortality.